TEKNIK WAWANCARA DALAM STORYTELLING UNTUK MENINGKATKAN KETERAMPILAN BERBICARA DAN MENYIMAK PADA PEMELAJAR BAHASA PRANCIS - Silvi Satiakemala (Jurnal SORA, 2019)
This research talks about the application of interview technique in Storytelling. The problems discussed in this research are the effectiveness and the contribution of interview technique in Storytelling in improving students’ speaking and listening comprehension skills. We use the quasi-experimental method to analyze data, using the pre-test and post-test and questionnaire as the finding aid. The results of the data analysis shows that the oral comprehension competencies increase thanks to learning scenarios using interview technique in Storyteling. The ability to speak and listen experienced good progress after comparing the results of the pre-test and post-test scores. Based on the results of data analysis we can conclude that the interview technique in Storytelling is effective in improving the speaking and listening skills of French learners.